The Composition Of The Catches Of Fishing Barrier Trap Gear (Belat) Day And Night In The Anak Setatah Village Districts West District Excitatory Riau Archipelago Meranti - Siregar, Ridwan Anhar; Brown, Arthur; ', Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study was conducted in may 2015 in anak setatah village in son regency of rangsang barat at kepulauan meranti regency the aim at this study look at difference catches in day and night of barrier trap gear (belat). the catches during the night is greater in respectively 100 kg and 13,6 kg. result of t-tes and chi square test show the difference of the and kind of species between day and night.Keywords: Composition, catches, Barrier Trap Gear